Genetic dissection of marker trait associations for grain micro-nutrients and thousand grain weight under heat and drought stress conditions in wheat - Devate, Narayana Bhat; Krishna, Hari; Mishra, Chandra Nath; Manjunath, Karthik Kumar; Sunilkumar, V. P.; Chauhan, Divya; Singh, Shweta; Sinha, Nivedita; Jain, Neelu; Singh, Gyanendra Pratap; Singh, Pradeep Kumar (Frontiers in Plant Science, 2023)
Wheat is grown and consumed worldwide making it an important staple food crop for both calorific and nutrient content. Micronutrient content especially grain Fe and Zn is at sub-optimal level causing malnutrition where wheat is staple food. Grain nutrient content is influenced by abiotic stress like drought and heat stress. The best method for addressing micronutrient deficiencies is biofortification of food crops. The prerequisites for marker assisted varietal development are the identification of the genomic region responsible for high grain Fe and Zn levels and an understanding of their genetics. A total of 193 diverse wheat genotypes were evaluated under drought and heat stress conditions across the years at IARI New Delhi, under timely sown irrigated (IR), restricted irrigated (RI) and late sown (LS) conditions. Grain iron (GFeC) and Zinc (GZnC) contents were estimated from both control and treatments. Genotyping of all the lines under study was done with the SNPs from 35K Axiom Breeder’s Array. Three sub group was observed in the association panel based on both PCA and dendrogram. A large whole genome LD block size of 3.49 M mb was observed. Genome wide association study identified 16 unique stringent marker trait associations for GFeC, GZnC and TGW. In-silico analysis depicted presence of 28 potential candidate gene genes in the flanking region of 16 linked SNPs such as Synaptotagmin-like mitochondrial-lipid-binding domain, HAUS augmin-like complex, Di-copper centre-containing domain, protein kinase, Chaperonin Cpn60, Zinc finger, NUDIX hydrolase etc. Expression level of these genes in vegetative tissues and grain were also found out. Utilization of identified markers in marker assisted breeding to rapid development of bio-fortified wheat genotypes to combat malnutrition.